The company of strangers : a natural history of economic life - Seabright, Paul (Princeton University Press, 2010)
The Company of Strangers shows us the remarkable strangeness, and fragility, of our everyday lives. This completely revised and updated edition includes a new chapter analyzing how the rise and fall of social trust explain the unsustainable boom in the global economy over the past decade and the financial crisis that succeeded it. Drawing on insights from biology, anthropology, history, psychology, and literature, Paul Seabright explores how our evolved ability of abstract reasoning has allowed institutions like money, markets, cities, and the banking system to provide the foundations of socia.